Pengaruh Price, Poduct Knowledge, Online Customer Review, dan Brand Image terhadap Pembelian Sunscreen Azarine oleh Generasi Z pada E-commerce Shopee - Mita Nurmala; Transistari, Ralina; Lazuardy, Ilman Taufiq (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2025)
This research aims to analyze the influence of price, product knowledge, online customer review, and brand image on the purchasing decision of Azarine sunscreen by generation Z on Shopee e-commerce. The research employs a purposive sampling method to select respondents, resulting in a sample size of 105 respondents. The study utilizes descriptive analysis and multiple liniear regression analysis to examine the data. Primary data were collected through questionnaire distribution and processed using SPSS software. The findings reveal that : (1) price has a positivde influence on the purchasing decision of Azarine sunscreen by generation Z on Shopee, (2) product knowledge has a positivde influence on the purchasing decision of Azarine sunscreen by generation Z on Shopee, (3) online customer review has a positivde influence on the purchasing decision of Azarine sunscreen by generation Z on Shopee, and (4) brand image has a positivde influence on the purchasing decision of Azarine sunscreen by generation Z on Shopee.